Pola Koalisi Partai Politik Dalam Penetapan Calon Kepala Daerah Kabupaten Toba Tahun 2024 - Sitorus, Yulita; Pasaribu, Ian; Putri, Revi Jeane; Efendi, Dori (Indonesian Democracy Research Center, 2025)
This study aims to analyze the coalition and non-coalition patterns that emerged in the 2024 Toba Regency Regional Election, focusing on the strategies employed by political parties in nominating candidates for regional head. Coalition and non-coalition political parties at the local level are crucial elements in determining the outcomes of the election, as structural factors such as legislative seat numbers, local voters, and the electability of candidate figures also influence the contest dynamics. Using a qualitative approach, this study examines how coalition formation or the decision to remain non-coalition is influenced by local political and social factors, as well as party strategies in responding to the new nomination threshold regulation set by the Constitutional Court. The results of this study indicate that in the 2024 Toba Regency Regional Election, large coalitions formed by major parties emphasize electoral efficiency based on seat calculations, while smaller coalitions focus more on shared social visions and change. Additionally, the non-coalition strategy adopted by the Nasdem Party illustrates the application of Rational Choice Theory, where the decision to run independently was driven by the electoral calculation and the strength of the candidate's figure. This study provides new insights into the development of coalition theory at the local level and how local factors influence the formation of electoral strategies in regional elections.